Simple Imaging Techniques for Plant Growth Assessment - Shinsuke Agehara (EDIS)
Quantification of plant phenotypic traits, such as height, width, stem diameter, and leaf area, is often performed manually in the field; however, these measurements can be performed more quickly and precisely through simple imaging techniques using an image processing program. This new 5-page publication of the UF/IFAS Horticultural Sciences Department, written by Shinsuke Agehara, describes simple imaging techniques for plant growth assessment using the public domain program ImageJ. https://edis.ifas.ufl.edu/hs1353